INNOVATIVE STRATEGIES TO IMPROVE THE QUALITY OF HUMAN RESOURCES THROUGH SKILL AND COMPETENCY DEVELOPMENT - Nur Wulan Intan Palupi; Dian Imami Mashuri; Achmad Yoki Febrima (International Journal of Management, Business, and Social Sciences, 2024)
Abstrack High-quality human resources (HR) represent invaluable assets for any organization, particularly in an era characterized by dynamic and competitive business environments. It is essential for companies not only to retain their human capital but also to continually enhance their quality. This enhancement encompasses not only technical skills but also encompasses comprehensive skill development and the nurturing of soft skills.This research adopts a literature review approach to delve into prior findings pertaining to the development of HR skills and competencies. Descriptive analysis is utilized to meticulously dissect library resources and scholarly materials. The primary objective of this research is to provide comprehensive insights into critical questions concerning objectives, implementation methodologies, and innovative strategies for fostering HR skills and competencies.By doing so, this research aims to equip organizations with valuable insights that can be instrumental in effectively managing HR, confronting rapidly evolving business challenges, and ultimately achieving corporate objectives. Through a thorough exploration of best practices and emerging trends in HR development, this research seeks to contribute to the body of knowledge that informs strategic HR management decisions in today's competitive landscape.